Immunogenicity and safety of the BNT162b2 mRNA COVID-19 vaccine in people living with HIV-1. (December 2021) - Levy, Itzchak; Wieder-Finesod, Anat; Litchevsky, Vladyslav; Biber, Asaf; Indenbaum, Victoria; Olmer, Liraz; Huppert, Amit; Mor, Orna; Goldstein, May; Levin, Einav Gal; Hod, Tammy; Cohen, Carmit; et al.
Abstract: Objectives: The immunogenicity and safety of the Pfizer-BioNTech BNT162b2 mRNA vaccine in people living with human immunodeficiency virus type 1 (PLWH) are unknown. We aimed to assess the immunogenicity and safety of this vaccine in PLWH. Methods: In this prospective open study, we enrolled 143 PLWH, aged ≥18 years, who attended our clinic and 261 immunocompetent health-care workers (HCWs). Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) receptor binding domain (RBD) IgG and neutralizing antibodies were measured. Adverse events, viral load and CD4 cell counts were monitored. Results: At a median of 18 days (interquartile range 14–21 days) after the second dose, anti-RBD-IgG was positive in 139/141 (98%) PLWH. Among HCWs, 258/261 (98.9%) developed anti-RBD-IgG at a median of 26 days (interquartile range 24–27 days) after the second dose. Following the second dose, immune sera neutralized SARS-CoV-2 pseudo-virus in 97% and 98% of PLWH and HCWs, respectively. Adverse events were reported in 60% of PLWH, mainly pain at the injection site, fatigue and headache. AIDS-related adverse events were not reported. Human immunodeficiency virus load increased in 3/143 (2%) patients from <40 copies/mL to ≤100 copies/mL. CD4 + T-cell count decreased from a geometric mean of 700 cells/μL (95% CI 648–757 cells/μL) to 633.8 cells/μL (95% CI 588–683 cells/μL) (p < 0.01). Conclusions: BNT162b2 mRNA vaccine appears immunogenic and safe in PLWH who are on antiretroviral therapy with unsuppressed CD4 count and suppressed viral load.